Beyond Beauty : Aesthetic Philosophy as a Tool for Liberatory Education - Graves, Kei, (Arts, Creativities, and Learning Environments in Global Perspectives ;, 2025)
What does it mean to live a life of beauty and liberation? In an era marked by divisive debates over curriculum, justice, and inclusion in education, this book calls us to return to a fundamental question: our shared humanity. This book is an integrative work weaving together the lived experiences of educators, critical pedagogy, aesthetic theories, sublimity, creativity, and feminist philosophies of social justice and antiracism. It advances our understanding of oppression by applying aesthetic frameworks to analyze, discuss, and dismantle dehumanizing systems. Aimed at educators, higher education faculty, and interdisciplinary scholars, this book bridges theory and practice. It provides actionable strategies for creating classrooms that encourage critical thinking, creative expression, and sustained engagement with liberatory principles. Examining how beauty and sublimity influence our understanding of justice and oppression, this book offers a fresh perspective on fostering transformative learning environments. Beauty has much to teach us about liberation. This text invites readers to explore the complexities of oppression while uncovering how education can leverage beauty and aesthetics to cultivate resilience, courage, and solidarity. For those committed to aligning educational practices with justice and human flourishing, this book offers both inspiration and a roadmap for change.